A Policy Framework for Promoting Financial Literacy in Iran - Ahmad Jahangir Feizabadi (تحقیقات مالی)
Objective Financial literacy is widely recognized as a crucial life skill, with individuals in developed countries expected to attain a desirable level of financial competence. This significance is reflected in the fact that more than 60 countries have developed national policies and strategies to promote financial literacy, incorporating specific programs into their agendas. Iran is no exception. Enhancing financial literacy is particularly important given the country's distinct economic, social, political, and cultural conditions. Improving individuals' financial awareness, knowledge, and skills reduces financial errors, strengthens sound financial decision-making, boosts confidence, and aids in achieving financial security and well-being. Furthermore, it can contribute to macroeconomic and social improvements, ensure economic stability, and foster greater public alignment with financial and economic policies. Therefore, it is essential to integrate this issue into the agendas of higher-level policymaking institutions and develop policies to promote financial literacy that are tailored to Iran's unique Islamic-Iranian culture.